Women's sports injuries: A bibliometric study of research trends and future perspectives - Ayona Eldos; Shamshadali Perumbalath; Vinu W (Apunts Sports Medicine)
Women's participation in sports has grown significantly, but concerns about sports-related injuries among female athletes persist. This study conducts a bibliometric analysis of women's sports injuries literature using data from 910 research articles retrieved from the Scopus database (1962 to July 2024). Employing Biblioshiny and VOSviewer, this study analyses performance and science mapping techniques to landscape the research overview. These findings delineate influential authors, impactful journals, and important articles. Also, identify the major areas of interest and suggest trending and future potential areas of research investigation in women's sports injuries. The study's implications support researchers, coaches, trainers, policymakers, and funding institutions in enhancing collaboration and prioritizing research on women's sports injuries. Recommendations include expanding this study to explore emerging research directions.